Rethinking the role of tv series: entertaining content, propaganda ways or new myth - M. I. Korobko (Ukrainian Cultural Studies, 2018)
The article is an overview of the problem of TV series as a mass culture phenomenon. The purpose of the article is an attempt to rethink the role of television series in the modern socio-cultural sphere, determining their role for humanity in general, and identifying ways for further research in this area. We understand mass culture as a very wide range of phenomena, which surround people every day, especially in the field of human leisure. There are various forms of leisure: walks, reading, watching TV series, etc. Today, we can talk about TV series as a cultural phenomenon that cannot be left out of the attention of academic circles because of the fact that TV shows are viewed by the vast majority of people around the world who have a TV or the Internet connection. Today, this genre of television performs not only an entertaining function, but also an educational, informational, propaganda function, etc. These days the TV series is no longer a mere entertainment for housewives. Netflix and HBO TV series exceeds all expectations, they are expensive, serious, interesting, historically reliable, they are beyond the so-called "low culture", evolving into something completely new. But what exactly? They are very similar in their construction to the new myth, they create new meanings, they form the consciousness of the new generation, now they are turning into a new type of communication and means of propaganda. Now it is not embarrassing to say that you love TV series. More and more foreign TV shows are being released for the intellectual elite. Is the series really not a guilty pleasure anymore? We cannot say with certainty that "they went to a higher league", but the fact is that they cause serious interest among contemporary culturologists, philosophers and sociologists. The series is an endless source for research by humanitarian scholars, and besides, it’s a good way to spend a free time after a hard work day.